2016
DOI: 10.1177/0950422216653198
|View full text |Cite
|
Sign up to set email alerts
|

Start-up entrepreneurs and university students in a co-learning mode

Abstract: Start-up companies have been recognized as key drivers of wealth and job creation. Many students now in universities will therefore find their future employment in start-up companies, or will found them. Success in the start-up environment requires a specific set of skills. There is a growing supply of university education for new venture creation and an increasing demand for interaction between universities and start-up ventures so that knowledge can be transferred between them. This article evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous research (Saukkonen, 2014;Saukkonen et al, 2016) has indicated that these collaborative learning set-ups have fostered students´ networks, entrepreneurial skills (measured via self-efficacy) and networks, adding to their entrepreneurial opportunities more than other individual stand-alone courses in the same institution.…”
Section: Journal Of Educational Issuesmentioning
confidence: 99%
“…Previous research (Saukkonen, 2014;Saukkonen et al, 2016) has indicated that these collaborative learning set-ups have fostered students´ networks, entrepreneurial skills (measured via self-efficacy) and networks, adding to their entrepreneurial opportunities more than other individual stand-alone courses in the same institution.…”
Section: Journal Of Educational Issuesmentioning
confidence: 99%